PENGARUH DOSIS DAN SAAT PEMBERIAN PUPUK P TERHADAP HASIL TANAMAN BUNCIS (Phaseolus vulgaris, L.) TIPE TEGAK - Eka Nuryani; Gembong Haryono; Historiawati Historiawati (Universitas Tidar, 2019)
This research is to study the result of dose and application time of P fertilizer on bean (Phaseolus vulgaris, L.) has been done in May to August 2018 in Ngleses village, Candimulyo district, Magelang regency. Altitude of 434 m above sea level, with latosol soil type and 6 of soil pH. The research was conducted as factorial experiment (4x2) arranged in a randomized complete block design, repeated three times. The 1st factor is Dose of P fertilizer : 58 kg/ha, 83kg/ha ,108kg/ha and 133kg/ha. The 2nd factor is application times of P fertilizer : 14 days and 21 days. Data should be analyzed with variance , orthogonal polynomial test for dose of P fertilizer and LSD test for application time of P fertilizer. Increasing of dose of P fertilizer will increased number of pods per plant (R2= 0.7193), weight of fresh pods per plant (R2= 0.702) and weight of fresh pods per m2 (R2= 0.8135).Application time of P fertilizer only gave highest yield on weight of fresh pods per m2. All parameters have the same respond for different dose of P fertilizer at different application tipe of P fertilizer.